International Activities Mondriaan Foundation : Annual Report 2001. - Luiten, Gitta; Mondriaan Stichting, Amsterdam (Amsterdam : Mondriaan Stichting, 2002)
Post, Liza May ; Raedecker, Michael ; Atelier van Lieshout ; Daan, Wendelien ; Martens, André ; Hoegen, Philippine ; Tan, Fiona ; Koelewijn, Job ; Ophuis, Ronald ; Mik, Aernout ; van Manen, Bertien ; Gaba, Meschac ; Tiong Ang
Engels
boek